1996
DOI: 10.1113/expphysiol.1996.sp003999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rearing temperature on perirenal adipose tissue development and thermoregulation following methimazole treatment of postnatal lambs

Abstract: SUMMARYThis study examined the effect of ambient temperature on perirenal adipose tissue development and thermoregulation over the first month of postnatal life in lambs treated with a drug that reduces thyroid hormone synthesis (methimazole; at a dose of 50 mg day-' (kg body weight)-').Twin lambs were hand-reared at a fixed level of nutrition in either a warm (WR; 25 'C) or cool (CR; 10-15 'C) ambient temperature. Oxygen consumption, heart rate and colonic temperature were measured during non-rapid eye moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…This could include a decrease in muscle UCP3 activity following feeding thereby minimizing the whole-body response to any rise in thermogenic response within BAT. The finding that CD lambs possessed BAT with a higher thermogenic activity despite a lower type II 5'monodeiodinase activity is in accord with our previous studies on normothermic lambs with normal plasma thyroid hormone concentrations (Symonds, Andrews, Buss, Clarke, Darby & Lomax, 1996). Furthermore, results from the present study indicate that in contrast to pigs, a species that does not possess BAT, changes in metabolism following feeding can be observed in the absence of any increase in heat production, thyroidal activity or sympathetic nervous activity (Sharman, Cooper, Dauncey & Ingram, 1986;Dauncey & Morovat, 1993;Herpin, Berthon, Bertin, De Marco, Dauncey & Le Dividich, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…This could include a decrease in muscle UCP3 activity following feeding thereby minimizing the whole-body response to any rise in thermogenic response within BAT. The finding that CD lambs possessed BAT with a higher thermogenic activity despite a lower type II 5'monodeiodinase activity is in accord with our previous studies on normothermic lambs with normal plasma thyroid hormone concentrations (Symonds, Andrews, Buss, Clarke, Darby & Lomax, 1996). Furthermore, results from the present study indicate that in contrast to pigs, a species that does not possess BAT, changes in metabolism following feeding can be observed in the absence of any increase in heat production, thyroidal activity or sympathetic nervous activity (Sharman, Cooper, Dauncey & Ingram, 1986;Dauncey & Morovat, 1993;Herpin, Berthon, Bertin, De Marco, Dauncey & Le Dividich, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Symonds et al [42] and Medica et al [41] also reported that plasma thyroid hormone concentrations decreased with advancing age. The signifi cantly lower serum T 3 and T 4 levels in separated lambs are parallel to the fi ndings of Cabello and Wrutniak [12] .…”
Section: Discussionmentioning
confidence: 94%
“…The signaling pathways atrophying BAT are not fully understood. The loss of newborn BAT is promoted by warm acclimation and inhibition of thyroid hormone secretion in precocial offspring (Brück and Wünnenberg 1966;Adamsons et al 1969;Darby et al 1996;Symonds et al 1996).…”
Section: Different Types Of Bat In Newbornsmentioning
confidence: 99%